Revisiting Social Learning and Cultivation Theories in the Digital Era - Tinuade, Ademola (BIRCU, 2026)
Research on media effects has long attempted to elaborate on how exposure to media content affects audience behavior and perceptions of social reality. Bandura’s Social Learning Theory and Gerbner’s Cultivation Theory are among the most essential theories in this tradition. This study carries out a conceptual and comparative analysis of these two fundamental theories in mass communication studies. Based on current scholarly studies, the study explores their origins, assumptions, limitations and applications, especially in modern digital and Nigerian media environments. Social Learning Theory describes how people pick up and learn behaviors through observational learning and modeling, while Cultivation Theory concentrates on long-term forming of perceptions through accumulated media exposure. Through critical evaluation, this study implies that even though both theories came to light in the traditional media period, they are still applicable in comprehending behavioral imitation and creation of perception in the period of social media, streaming platforms and algorithm driven content. This study also suggests an integrated conceptual framework that combines behavioral and perceptional aspects of media influence, thereby improving theoretical comprehension of media effects in modern society.